108k views
0 votes
What is the solution to -2(3x - 9) + 5x = -10?
-8
8
28

User Meiryo
by
5.2k points

2 Answers

6 votes

Answer:

X = 28

Explanation:

multiply the parenthesis by -2 to get

-6x + 18 + 5x = -10

collect the like terms, -6 + 5x

-x + 18 = -10

subtract 18 from both sides to get X alone

-x = -10 - 18

-x = -28

change the signs


x = 28

User Ivo Wetzel
by
5.0k points
4 votes

Answer:

x = 28

Explanation:

distribute the parenthesis on the left side by - 2

- 6x + 18 + 5x = - 10

- x + 18 = - 10 ( subtract 18 from both sides )

- x = - 28 ( multiply both sides by - 1 )

x = 28


User Andre Guerra
by
5.2k points